2014
DOI: 10.1186/1472-6963-14-135
|View full text |Cite
|
Sign up to set email alerts
|

Disaster resilience in tertiary hospitals: a cross-sectional survey in Shandong Province, China

Abstract: BackgroundHospital disaster resilience can be defined as a hospital’s ability to resist, absorb, and respond to the shock of disasters while maintaining critical functions, and then to recover to its original state or adapt to a new one. This study aims to explore the status of resilience among tertiary hospitals in Shandong Province, China.MethodsA stratified random sample (n = 50) was derived from tertiary A, tertiary B, and tertiary C hospitals in Shandong Province, and was surveyed by questionnaire. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 23 publications
0
72
0
2
Order By: Relevance
“…Such inadequacy may impede the ability of the rescue teams to provide first-line medical treatment during future natural disasters (31). Emergency supplies are also an essential component of hospital disaster preparedness (28). While one study recently found that more than 75% of tertiary hospitals in the Shandong Province had stockpiles of emergency supplies (e.g.…”
Section: Disaster Preparednessmentioning
confidence: 99%
“…Such inadequacy may impede the ability of the rescue teams to provide first-line medical treatment during future natural disasters (31). Emergency supplies are also an essential component of hospital disaster preparedness (28). While one study recently found that more than 75% of tertiary hospitals in the Shandong Province had stockpiles of emergency supplies (e.g.…”
Section: Disaster Preparednessmentioning
confidence: 99%
“…Zhong in the study of resilience against disasters in 50 hospitals in China argued that assessing the risks that threaten the region as well as having an organized plan to discharge patients and vulnerable population of the region are among important approaches within the framework of hospital safety [19]. The results of Sabzeghabaei study on the status of safety and readiness in selected hospitals of Shahid Beheshti University of Medical Sciences and Mirzaee study in Ilam hospitals against disasters showed that the safety level is moderate in most hospitals [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, R5 affirmed that the hospitals' top management should establish and endorse the policy, assessment tool or framework related to disaster resilient hospital. It is due to the fact that, it could serve as guidelines to the hospitals' stakeholders in achieving disaster resilient hospital (Zhong et al, 2014). The guidelines, assessment tool or framework should encompass for mitigation, preparedness, response and recovery in order to absorb, easily adapt to the disaster and able to recover quickly.…”
Section: R6mentioning
confidence: 99%